An analysis of the structure, actors and interrelationships producing Luxembourg's ICT ecosystem - Nico Binsfeld; Jason Whalley; Lee Pugalis (International Telecommunications Society (ITS), 2017)
There is substantial analytical value in examining the structure of the ICT sector by deploying the notion of ecosystems, which can help to reveal new insights into the role of key actors and their interrelationships. This paper aims to provide a thorough analysis of Luxembourg's ICT ecosystem, which until now has received limited research attention in the international arena. Key actors comprising and producing the ecosystem are identified and analysed according to a layered model devised by Martin Fransman (2001). The primary output is a detailed mapping of the Luxembourgish ICT ecosystem. The findings indicate that Luxembourg's ICT ecosystem consists of nearly 2000 different actors of which the majority are micro and small software development companies. Nevertheless, some large telecommunications network operators in which the government holds a substantial stake appear to perform a decisive role from an economic perspective. More recently, the role of different types of service providers, particularly subcontractors to financial actors, has grew in prominence, with trends suggesting that this is subject to continue. The research has also identified some limitations to the Fransman model and suggests several extensions as well as a stakeholder analysis to gain a deeper understanding of the issues at stake. It is intended to be of use and interest to policymakers, managers, and decision makers or actors operating within and across different layers of ICT ecosystems.
Keywords: L86; L88; 330; Luxembourg; ICT; ecosystems; Fransman